Status of Vitamin D among People Visiting a Tertiary Care Center of Eastern Nepal: A Hospital-Based Study (Journal of Nobel Medical College, 2021)
Background: Vitamin D deficiency is a serious health-problem worldwide and the estimation of its plasma concentration is crucial. The study aims to determine the circulating levels of vitamin D in patients visiting Birat Medical College Teaching Hospital, one of the tertiary care centers of Eastern Nepal.Materials and Methods: It was descriptive cross-sectional study conducted in the Department of Biochemistry at Birat Medical College Teaching Hospital, Nepal. From the hospital registry, clinical data of 250 patients including their age, gender and serum 25-hydroxy vitamin D was retrieved for the four months of May – August, 2021. The vitamin D status was classified as deficiency (